2016
DOI: 10.1097/brs.0000000000001599
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Validity, and Cross-Cultural Adaptation of the Turkish Version of the Bournemouth Questionnaire

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…The Pearson's correlation coefficient values showed that the correlation of the Turkish version of ProFitMap-neck with the NDI and VAS was high. In the Br-Portuguese version of the ProFitMap-neck, the correlation values between the domains of the Br-ProFitMap-neck and NDI varied from 0.56 to 0.71 [24]. The results of our study were similar to those for the Br-Portuguese version of the ProFitMap-neck.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The Pearson's correlation coefficient values showed that the correlation of the Turkish version of ProFitMap-neck with the NDI and VAS was high. In the Br-Portuguese version of the ProFitMap-neck, the correlation values between the domains of the Br-ProFitMap-neck and NDI varied from 0.56 to 0.71 [24]. The results of our study were similar to those for the Br-Portuguese version of the ProFitMap-neck.…”
Section: Discussionsupporting
confidence: 80%
“…As a result, it appears that the Turkish version of the ProFitMap-neck is highly stable over time. The ICC values ranged from 0.81 to 1 in the Br-Portuguese version of ProFitMap-neck [24]. The researchers indicated that the Br-ProFitMap-neck had high levels of reliability for total score and indices.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it is important to present the Turkish version of the NBQ in the literature for using it in clinical practice and research. For the questionnaire validation studies, it is recommended to select the questionnaires which are validated, considered to be the gold standard and context specific if possi- ble [25]. Therefore, one of the questionnaires that we chose in the validation study of the NBQ was the NDI, in which the Turkish validity and reliability study was conducted [24].…”
Section: Discussionmentioning
confidence: 99%
“…Item total correlation and item-deleted Cronbach's alpha coefficient were calculated during this analysis. If this value is above 0.80, it indicates excellent reliability [25].…”
Section: Reliabilitymentioning
confidence: 99%